IMPLEMENTASI APLIKASI MOBILE JKN BPJS KESEHATAN CABANG SUKABUMI 2018 – 2021 - Irvan Maulana; Yana Fajar FY Basori; Dine Meigawati (LPPM Universitas Djuanda Bogor, 2023)
The research was aimed at finding out the implementation of the Mobile JKN BPJS Kesehatan Sukabumi Branch in 2018 – 2021. The method deployed was qualitative method with narrative approach. The techniques of collecting data conducted were observation, interviews, documentation, and audio-visual materials. The results of the research show that the implementation of the Mobile JKN application at BPJS Kesehatan Sukabumi Branch in 2018-2021 less optimal procedures or methods used BPJS Kesehatan Cabang Sukabumi, yet to determine human resources (special, massive, focused) in socializing Mobile JKN application, lacking information for the users as there are people and participants who know and do not know the Mobile JKN application itself which turns out to be influenced by the information obtained about the Mobile JKN application, less up to date as the Mobile JKN platform is still in the old version, and in using the application there are those who are able to use the app independently and those who still have difficulty in using the Mobile JKN application. Supporting and inhibiting factors depend on human resources, system resources and environment, either BPJS Kesehatan itself or the people in general and the participants.